Language acquisition in the theological classroom: A case study in comprehensible input - Westengard, Brandon L. (Teaching theology and religion, 2023)
Languages have played a significant role in the shaping of theological and religious leaders. Historically consisting mostly of biblical and ancient languages, contemporary theological education includes the study of modern foreign languages for research and ministerial purposes. If written and spoken communication in a variety of languages is a foundational aspect of the theological classroom, why is it, then, that seminaries and theological institutions give little attention to theories and pedagogies of second language acquisition? This article seeks to expose theological educators to the most significant theory in the study of language pedagogy and provides a case study of a course taught to students in a seminary setting. In addition to scholarly studies, it relies on the influence of autodidactic polyglots, an indispensable source of experience and wisdom in the world of language acquisition. By improving practices around language instruction, the future of theological education can better engage with a multi-cultural and global society.